2011
DOI: 10.1016/j.bbadis.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Beta2-adrenergic receptor regulates cardiac fibroblast autophagy and collagen degradation

Abstract: Autophagy is a physiological degradative process key to cell survival during nutrient deprivation, cell differentiation and development. It plays a major role in the turnover of damaged macromolecules and organelles, and it has been involved in the pathogenesis of different cardiovascular diseases. Activation of the adrenergic system is commonly associated with cardiac fibrosis and remodeling, and cardiac fibroblasts are key players in these processes. Whether adrenergic stimulation modulates cardiac fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
93
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 40 publications
5
93
0
1
Order By: Relevance
“…Our data provide the first evidence that TGF-␤1 promotes the intracellular degradation of Col-I via autophagic process to regulate the levels of Col-I. Others had previously reported that autophagy induced by the activation of ␤ 2 -adrenergic receptors enhanced the degradation of collagen in cardiac fibroblasts (10). Rapamycin, which induces autophagy by inhibiting mTOR, enhanced elimination of aggregated procollagen (9).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Our data provide the first evidence that TGF-␤1 promotes the intracellular degradation of Col-I via autophagic process to regulate the levels of Col-I. Others had previously reported that autophagy induced by the activation of ␤ 2 -adrenergic receptors enhanced the degradation of collagen in cardiac fibroblasts (10). Rapamycin, which induces autophagy by inhibiting mTOR, enhanced elimination of aggregated procollagen (9).…”
Section: Discussionmentioning
confidence: 51%
“…In heat shock protein 47 (Hsp47)-null cells, the deletion of collagen-specific molecular chaperone Hsp47 results in misfolded type I procollagens that are subjected to intracellular degradation via autophagy (9). Furthermore, enhanced degradation of Col-I correlated with increase in autophagy when the ␤ 2 -adrenergic receptor is activated in cardiac fibroblasts (10). These data strongly suggest that autophagy plays a role in the turnover of ECM through intracellular degradation of Col-I.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Carbachol was utilized to stimulate saliva production in this study, since Ipr has been shown to regulate autophagy in certain tissues (Aránguiz-Urroz et al, 2011). The results of accumulated MUC5B in SLGs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy attenuates endoplasmic reticulum stress by eliminating misfolded procollagen [24] . Furthermore, Beta (2)-adrenergic stimulation triggers autophagy in cardiac fibroblasts and promotes intracellular collagen degradation and inhibits cardiac fibrosis [25] . However, this effect has been demonstrated in other organs, and whether it exhibits the same effect in liver remains unclear.…”
Section: Autophagy and Collagen Degradationmentioning
confidence: 99%